Conceptualizing A Critical Thinking Learning Transfer Model: A Qualitative Approach - Noor Azura Mat Said; Siti Mariam Bujang; Nor Aishah Buang; Harlina Halizah Siraj @ Ramli; Mohd Nasri Awang Besar (111Malaysian Journal of Learning and Instruction, 2024)
112Malaysian Journal of Learning and Instruction, 18, No. 1 (January) 2021, pp: 111-130